2013
DOI: 10.4236/pp.2013.43042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclooxygenase-2 Blockade on Renal Hypertrophy Development during Early Diabetes Mellitus

Abstract: Diabetes mellitus is the leading cause of diabetic nephropathy; the early phase of diabetes is associated with kidney growth and hyperfiltration; several factors modulate these changes, among them, prostaglandins and angiotensin II. Previous studies have shown that cyclooxygenase-2 is implicated in experimental models of diabetes. The aim of this work was to study the effect of celecoxib treatment on renal hypertrophy development in early diabetes mellitus. In our rats with early streptozotocin-induced diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Others showed that COX-2 overexpression is involved in progressive renal injury in a model of nephropathy induced by renal ablation in rats, since the chronic inhibition of COX-2 attenuates the damage, reducing glomerular hypertension, and renal inflammation. 14 Similarly, treatment with celecoxib, a selective COX-2 inhibitor, prevented the increase in the cellular area in proximal tubules and renal protein/DNA ratio in diabetic rats, 59 indicating that COX-2 is involved in the development of renal hypertrophy in diabetes. Additionally, it was reported that COX-2 promotes mesangial cell proliferation in culture under stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Others showed that COX-2 overexpression is involved in progressive renal injury in a model of nephropathy induced by renal ablation in rats, since the chronic inhibition of COX-2 attenuates the damage, reducing glomerular hypertension, and renal inflammation. 14 Similarly, treatment with celecoxib, a selective COX-2 inhibitor, prevented the increase in the cellular area in proximal tubules and renal protein/DNA ratio in diabetic rats, 59 indicating that COX-2 is involved in the development of renal hypertrophy in diabetes. Additionally, it was reported that COX-2 promotes mesangial cell proliferation in culture under stress conditions.…”
Section: Discussionmentioning
confidence: 99%